Perbandingan VDF Jembatan Timbang Tanjung Balik Terhadap VDF MDPJ 2017 Berdasarkan Beban Aktual: Comparison of the Tanjung Balik Weighing Bridge VDF against the 2017 MDPJ VDF Based on Actual Loads - Erzag, Almira Nabila; Sentosa, Leo; Putra, Benny Hamdi Rhoma (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2023)
The 2017 Road Pavement Design Manual is a basic reference for road pavement planning in Indonesia, with the provision of a tolerance limit for the overload of 50%. However, the case of violation of the overload that occurs causes a significant increase in the damage to the road. The purpose of this research is to assess the validity of the VDF value in the 2017 MDPJ. This study uses vehicle weight data obtained from UPPKB Tanjung Balik West Sumatra by classifying vehicles, calculating each load distribution, and calculating the VDF value as a value that will be compared to the VDF that has been set in the 2017 MDPJ. Based on the analysis carried out, the VDF values ​​for each vehicle class 6a, 6b, 7a, and 7b were 0.39, 8.17, 9.28, and 4.53, with the determination of the VDF value in the 2017 MDPJ was 0.5, 3.0, 9.8, and 36.9. From these results, it is concluded that the VDF value in vehicle class 6b does not meet the VDF value that has been set so it is necessary to make corrections to the manual.